Fluorescent hollow mesoporous carbon spheres for drug loading and tumor treatment through 980-nm laser and microwave co-irradiation. (July 2020) - Gui, Xin; Chen, Yang; Zhang, Zheyu; Lei, Longfei; Zhu, Fangliang; Yang, Wenxuan; Guo, Yuliang; Chu, Maoquan
Abstract: Hollow mesoporous particles for drug delivery and cancer therapy have attracted significant attention over recent decades. Here, we develop a simple and highly efficient strategy for preparing fluorescent hollow mesoporous carbon spheres (HMCSs). Compared with typical carbon materials such as fullerene C60, carbon nanotubes, reduced graphene oxide, and carbon nanohorns; HMCSs showed fewer effects on cell cycle distribution and lower toxicity to cells. Ten different drugs were incorporated into the HMCSs, and the maximum loading efficiency reached 42.79 ± 2.7%. Importantly, microwaves were found to improve the photothermal effect generated by HMCSs when combined with 980-nm laser irradiation. The cell killing and tumor growth inhibition efficiencies of HMCSs and drug-loaded HMCSs under co-irradiation with laser and microwaves were significantly improved compared with those under laser irradiation alone. After local administration HMCSs were only distributed in tissue at the injection site. HMCSs showed almost no toxicity in mice after local injection and could be completely removed from the injection site.